Wilms' tumor 1 peptide‐loaded dendritic cell vaccination in patients with relapsed or refractory acute leukemia. Issue 3 (10th March 2022) - Ogasawara, Masahiro; Miyashita, Mamiko; Yamagishi, Yuka; Ota, Shuichi
Abstract: Introduction: The prognosis of patients with relapsed or refractory acute leukemia is poor. In the present pilot study, we treated relapsed or refractory acute leukemia patients with Wilms' tumor 1 (WT1) peptide‐loaded dendritic cells (DCs) and examined safety, clinical and immunological responses. Methods: Eleven eligible patients were enrolled. DCs were administered every 2–3 weeks with OK‐432 adjuvant. Results: The treatment was well tolerated. The reduction of leukemia cells or the expression of WT1 mRNA was observed in four patients which was maintained for a significant period of time. All the responding patients manifested immune responses against WT1 which might be related to clinical outcome. Decreases in the absolute number of regulatory T cells were observed following vaccination, indicating that DC vaccinations may contribute to the reversal of immunosuppression. Conclusion: These results indicate that DC‐based immunotherapy is safe and feasible for patients with acute leukemia.